Computational gas-solids flows and reacting systems : theory, methods and practice - Pannala, Sreekanth, 1971-; Syamlal, Madhava; O'Brien, Thomas J. 1941- (Engineering Science Reference, 2011)
"This book provides various approaches to computational gas-solids flow and will aid the researchers, graduate students and practicing engineers in this rapidly expanding area"--Provided by publisher